2014
DOI: 10.1080/13683500.2014.932757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sustainable management policies on tourism companies' performance: the case of the metropolitan region of Madrid

Abstract: The adoption of sustainable management practices is booming among service companies, whether due to pressure exerted by external agents or the internal perception that not being aligned with sustainability distances companies from clients and puts companies' long-term prospects at risk. However, few studies have examined the combined effect of implementing environmental management practices and corporate social responsibility practices in the tourism sector. By analysing two surveys conducted with the managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…These assertions require further research. In part, this conclusion is aligned with previous studies that do not find a positive relationship between QMPs and FP in the tourism sector (Bagur-Femenías, Martí et al, 2015;Llach, Perramon et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These assertions require further research. In part, this conclusion is aligned with previous studies that do not find a positive relationship between QMPs and FP in the tourism sector (Bagur-Femenías, Martí et al, 2015;Llach, Perramon et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Along these lines, Bagur-Femenías, Martí et al (2015) found that EMP practices had a direct and significant effect on a company's competitiveness and on financial results, but different tourist industries have different levels of implementation. Thus, hotels had higher levels of environmentally friendly practices (Pereira-Moliner et al, 2012) compared with restaurants (Alonso-Almeida, 2013; Perramon et al, 2014) and travel agencies (BagurFemenias, Perramon, & Amat, 2015).…”
Section: Influence Of Emps On Small Companiesmentioning
confidence: 95%
“…QMP implementation can act as a positive signal for the market when the QMP is considered as a strategic bet on continuity and differentiation, thus creating competitive advantages and barriers to entry for potential consumers (Alonso-Almeida et al, 2012;Bagur-Femenías, Martí, & Rocafort, 2015).…”
Section: Adoption Of Qmps and External Improvements In The Organisationmentioning
confidence: 99%
“…Articles in the CSR and performance domain prioritize the organizational and financial outcomes of CSR activities (e.g., Bagur-Femenías et al, 2015;Youn et al, 2015). This is another well-researched topic in hospitality (Farrington et al, 2017) and management studies (Aguinis & Glavas, 2012).…”
Section: Thematic Perspective: Different Levels Of Analysismentioning
confidence: 99%